2020
DOI: 10.3168/jds.2019-17545
|View full text |Cite
|
Sign up to set email alerts
|

Body weight of dairy heifers is positively associated with reproduction and stayability

Abstract: This study investigated the relationships between body weight (BW) and stayability, and BW and calving pattern, of 189,936 New Zealand dairy heifers. Heifers were classified into 5 breed groups: Holstein-Friesian (F), Holstein-Friesian crossbred (FX), Jersey (J), Jersey crossbred (JX), and Holstein-Friesian × Jersey crossbred (FJ). Body weight was predicted using Legendre polynomials at 6, 12, and 15 mo of age, and we analyzed their relationships with stayability, calving rate, and re-calving rate over the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Jenko et al, 2013 Stayability A measure of cow survival that does not require recording of cull data. Handcock et al, 2020 The probability of a cow remain in the herd enough time to raise a certain number of calves that pay for her development and maintenance costs. Costa et al, 2020 The ability of the cow to calve at least three times until 76 months of age.…”
Section: Longevitymentioning
confidence: 99%
“…Jenko et al, 2013 Stayability A measure of cow survival that does not require recording of cull data. Handcock et al, 2020 The probability of a cow remain in the herd enough time to raise a certain number of calves that pay for her development and maintenance costs. Costa et al, 2020 The ability of the cow to calve at least three times until 76 months of age.…”
Section: Longevitymentioning
confidence: 99%
“…However, longterm benefits have also been reported. Heifers that are well grown, and heifers that get pregnant early in the breeding season, calve earlier and have improved lifetime production and reproduction (Pryce et al, 2007;Wathes et al, 2014;Dennis et al, 2018;Handcock et al, 2020). The extent and consistency of benefits under commercial conditions requires a larger data set to quantify the benefits under commercial environments.…”
mentioning
confidence: 99%
“…However, other studies have indicated that underconditioned heifers also have poor reproductive outcomes. A recent study reported an intermediate optimum for the relationship of BW at 15 mo of age with the proportion of animals that calved within the subsequent calving window (Handcock et al, 2020). Cows genetically inclined toward low BW during peak lactation also have poorer fertility due to an inability to maintain body condition (Pryce et al, 2001;Frigo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%